Loss of JAK1 Drives Innate Immune Deficiency - Witalisz-Siepracka, Agnieszka; Klein, Klara; Prinz, Daniela; Leidenfrost, Nicoletta; Schabbauer, Gernot; Dohnal, Alexander; Sexl, Veronika (Frontiers in Immunology, 2019)
The Janus kinase - signal transducers and activators of transcription (JAK-STAT) signaling pathway is critical in tuning immune responses and its dysregulation is tightly associated with cancer and immune disorders. Disruption of interleukin (IL)-15/STAT5 signaling pathway due to the loss of IL-15 receptor chains, JAK3 or STAT5 leads to immune deficiencies with natural killer (NK) cell abnormalities. JAK1, together with JAK3 transmits signals downstream of IL-15, but the exact contribution of JAK1 to NK cell biology remains to be elucidated. To study the consequences of JAK1 deficiency in NK cells, we generated mice with conditional deletion of JAK1 in NKp46+ cells (Jak1fl/flNcr1Cre). We show here that deletion of NK cell-intrinsic JAK1 significantly reduced NK cell numbers in the bone marrow and impaired their development. In line, we observed almost a complete loss of NK cells in the spleen, blood and liver, proving a crucial role of JAK1 in peripheral NK cells. In line, Jak1fl/+Ncr1Cre mice showed significantly impaired NK cell-mediated tumor surveillance. Our data suggest that JAK2 is not able to compensate for the loss of JAK1 in NK cells. Importantly, conditional deletion of JAK2 in NKp46+ cells had no effect on peripheral NK cells revealing that NK cell-intrinsic JAK2 is dispensable for NK cell survival. In summary, we identified that loss of JAK1 in NK cells drives innate immune deficiency, whereas JAK2 deficiency leaves NK cell numbers and maturation unaltered. We thus propose that in contrast to currently used JAK1/JAK2 inhibitors, the use of JAK2-specific inhibitors would be advantageous for the patients by leaving NK cells intact.